Enantioselectivity-Evaluation of Chiral Copper(II) Complexes Coordinated by Novel Chiral Tetradentate Ligands for Free Amino Acids by Mass Spectrometry Coupled With the Isotopically Labeled Enantiomer Method - Nakakoji, Takashi; Yoshino, Kaori; Izutsu, Kazuki; Sato, Hirofumi; Miyake, Hiroyuki; Mieda, Eiko; Shinoda, Satoshi; Tsukube, Hiroshi; Kawasaki, Hideya; Arakawa, Ryuichi; Ono, Daisuke; Shizuma, Motohiro (Frontiers in Chemistry, 2020)
A series of copper(II) complexes with chiral tetradentate ligands, N,N′-ethylene- bis(S-amino acid methyl amide or methyl ester) prepared from S-alanine, S-phenylalanine, S-valine or S-proline, was generated in methanol. The copper complexes provided three component complexes in the presence of a free chiral amino acid. The enantioselectivity for the amino acid was evaluated by electrospray ionization-mass spectrometry coupled with the deuterium-labeled enantiomer method and these copper complexes were found to exhibit high enantioselectivity for free amino acids having bulky side chains. This result suggests that steric interaction between the tetradentate ligand and free amino acid was a major factor in chiral recognition. The copper complex with a chiral tetradentate ligand prepared from S-proline showed opposite enantioselectivity to copper complexes consisting of tetradentate ligands prepared from other S-amino acids. The conformational difference of the tetradentate ligand in the copper complex was found to be significant for enantioselectivity.